The concept and typology of political parties and party systems. - Martsikhiv, Kh. R.; Voitovych, V. Yu.; Марціхів, Х. Р.; Войтович, В. Ю. (ВД "Гельветика", 2021)
Для сучасних держав роль політичних партій в організації державної влади є надзвичайно важливою темою, оскільки вони є основою належного функціонування якісної системи державного управління. Вони відіграють важливу роль у навчанні та просуванні кадрів у державній політиці, для чого вони є специфічним соціальним ліфтом. Тому вирішення проблем функціонування політичних партій в організації державної влади є, на нашу думку, доцільним питанням для тих країн, які будують демократію. Ретельне вивчення особливостей політичних партій є надзвичайно важливим для розуміння загальних тенденцій політичного процесу. Тому у статті розглянуто питання, пов’язані з визначенням сутності поняття «політична партія», також досліджено, що таке партійна система, її типологія та чинники, що впливають на її встановлення. Проаналізовано процес становлення теорії політичних партій та партійних систем. З’ясовано, що найуживанішим критерієм класифікації партійних систем є кількість партій, які змагаються, що вимірюється показником ефективної кількості партій. Визначено характеристики сучасних політичних партій, їхні функції в політичному процесі. Розгля нуто проблеми функціонування політичних партій, оскільки існування та діяльність політичних пар тій більшості сучасних держав є загальновизнаною нормою та трактується як невіід’ємний атрибут демократичного способу здійснення державного управління. Зроблено висновок, що все частіше політичні партії беруть участь у процесі прийняття рішень на всіх рівнях. Встановлено, що специфікою реалізації державної політики та метою соціального партнерства у світовій практиці є партнерство політичних партій та органів державної влади. Підтверджено, що співпраця державних установ та політичних пар тій для вирішення конкретних питань у світлі громадської думки є звичайною практикою демократичного політичного процесу.

The functioning of political parties in society is characterized. The study of this institution, a thorough study of the problems associated with it, is revealed. In modern conditions, the role of a political party in the organization of state power is considered as an extremely important topic for the countries of the post-communist camp, including Ukraine. Solving the problems of political structuring and establishing the institution of a parliamentary majority in political practice which led to a change in the role and social status of political parties, primarily their participation in shaping and identifying political will of citizens and implementing effective mechanisms of political accountability of parliament and government is analyzed. Political parties are investigated as the basis for the proper functioning of a quality system of public administration. A key role of political parties in training and promotion in public policy, for which they are a specific social elevator, is identified. The parties controlling mechanism of nominating their candidates in the elections is characterized. Parties’ influence on the political views and orientations of people, especially young people is analyzed. Par ties’ function of political socialization of citizens is defined. The article considers issues related to the definition of the essence of the concept of a political party, as well as examines what is a party system, its typology and the factors influencing its establishment. The process of formation of the theory of political parties and party systems is analyzed. It has been found that the most common criterion for classifying party systems is the number of competing parties, as measured by the effective number of parties. The characteristics of modern political parties, their functions in the political process are determined. The influence of the party system on the formation of the principles of public administration in democratic and transitional societies is analyzed. The problems of functioning of political parties are considered, as the existence and activity of political parties of most modern states is a generally accepted norm and is interpreted as an integral attribute of a democratic way of public administration. It is concluded that more and more often political parties are involved in the decision-making process at all levels. The specifics of the implementation of state policy and the purpose of social partnership in world practice are the partnership of political parties and public authorities. The cooperation of government institutions and political parties to address specific issues in the light of public opinion is a common practice in a democratic political process.
Поняття і типологія політичних партій та партійних систем.
Марціхів Х. Р. Поняття і типологія політичних партій та партійних систем / Х. Р. Марціхів, В. Ю. Войтович // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голова ред. ради), Л. І. Кормич (голов. ред.), І. М. Милосердна (відп. ред.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Видавничий дім «Гельветика», 2021. – Вип. 68. – С. 5-11. DOI https://doi.org/10.32837/app.v0i68.1278
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; типи партійних систем; політичні партії; державна політика; державне управління; критерії партій; types of party systems; political parties; public policy; public administration; party criteria